KRITIK AL-HAKIM ATAS BARAT DAN TIMUR DALAM NOVEL ’USFUR MIN AL-SYARQ - Uki Sukiman (Sunan Kalijaga State Islamic University Yogyakarta, 2011)
The clash between Eastern and Western civilization has always been a topic of interest with various responses. Egypt is one of the countries, which has this response. This can be seen from Taufiq al-Hakim’s “Usfur min al-Syarq”. The scholars of modern Egypt thought have divided these responses into three groups: the conservatives, the Westernists, and the moderates. The conservatives tend to preserve the indigenous cultures. The Westernists try to westernize the indigenous cultures, while the moderates hybridize the culture. Through Abrams’ categorization, al-Hakim’s thought can be formulated in three developments. Firstly, the progress of those two civilizations has different directions. Each has its own advantages: the Western deals with earth and the Eastern with heaven. Secondly, the Eastern loses its identity if the Western dominates. Thirdly, al-Hakim hybridizes the positive sides of the two poles.